1986
DOI: 10.1177/107554708600800201
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Health. After joining the NIMH in 1963, he held a number of increasingly responsible positions in the areas of applied and services research, and knowledge transfer. As shall become clear through reading these &dquo;essays in tribute,&dquo; Howard R. Davis, or &dquo;Howie&dquo; as he was called, was a man large in intellect and spirit, as well as physical size. He was a scholar intent on discerning what he referred to as &dquo;reliable knowledge,&dquo; blessed with an artist's sensitivities and a creative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In either circumstance, society's attempt to address and respond to victims has been damaging (Salasin, 1981).…”
Section: Shock and Denialmentioning
confidence: 99%
See 2 more Smart Citations
“…In either circumstance, society's attempt to address and respond to victims has been damaging (Salasin, 1981).…”
Section: Shock and Denialmentioning
confidence: 99%
“…This research attempted to study victims with the recognition that they may have special problems and needs because of their status as a victim (Salasin, 1981). The presentation of data as expressed by participants in this study provided another opportunity to narrow the gap found in victim studies regarding needs.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation